PENGARUH EMPLOYEE ENGAGEMENT KARAKTERISTIK INDIVIDU DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR KECAMATAN MEDAN BELAWAN - Ahmad . (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The formulation of the problem in this study is how the influence of employee engagement on employee performance. How does the influence of individual characteristics on employee performance. How is the influence of work discipline on employee performance. How does the influence of employee engagement individual characteristics and work discipline on employee performance.The purpose of this study was to determine the effect of employee engagement on employee performance. To determine the effect of individual characteristics on employee performance. To influence the influence of work discipline on employee performance. To influence employee engagement individual characteristics and work discipline on employee performance.The sample in this study amounted to 47 people. Data analysis techniques in this study used descriptive analysis and multiple linear regression analysis.The results of this study explain that employee engagement has a positive and significant  effect  on  employee  performance.  Individual  characteristics  have  a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Employee engagement of individual characteristics and work discipline has a positive and significant effect on employee work performance.